Delayed Repair of Hemitruncus in an Extremely Low Birth Weight Infant. (8th August 2011) - Godown, Justin; Baker, Cynthia; Kuhn, Nicole; Brown, Karla; Buck, Scott; Mill, Michael; Price, Wayne
ABSTRACT: We present a case of a premature female infant, with a delayed diagnosis of hemitruncus, who underwent primary repair at 105 days of life. There have been few published reports of premature infants with hemitruncus, and none to our knowledge who underwent repair that was significantly delayed.